The Mechanism of Word of Mouth in the Transformation of Strategic Capabilities Into Competitive Advantages of Excellent Private Universities the Role of Word of Mouth as a Conversion Mechanism in the Digital Age (Parsimonious Model) - Petiana Indriati; Sri Widyastuti; Zulkifli Zulkifli (Green Publisher Indonesia, 2026)
The changing competitive landscape of private higher education institutions (PTS) indicates that institutional excellence is no longer solely determined by internal performance, but rather by how that performance translates into credible public perception. This study aims to examine the role of Word of Mouth (WoM) as a conversion mechanism that transforms strategic capabilities—student experience (X1), digital strategy (X2), and industry partnerships (X3)—into competitive advantage (Y1) at Unggul-accredited PTS in the Greater Jakarta area. The research approach employs an explanatory quantitative method with Structural Equation Modeling analysis based on Partial Least Squares (SEM-PLS). Data were obtained from 252 respondents consisting of active students and alumni. The results show that student experience and digital strategy have no direct effect on competitive advantage, while industry partnerships have a significant positive effect. However, all strategic capabilities are proven to have a significant effect on Word of Mouth, and Word of Mouth has a strong effect on competitive advantage. Mediation tests confirm that WoM functions as the main transmission mechanism, with a full mediation pattern for student experience and digital strategy, and partial mediation for industry partnerships. This finding confirms that strengthening internal capabilities needs to be accompanied by a social-digital advocacy activation strategy to produce a competitive advantage that is recognized by the public.